Penggunaan Algoritma Vigenere Cipher dan RSA (Rivest-Shamir-Adleman) Untuk Keamanan Data Pembelian di PT Lamongan Marine Industry - Fifin Nur Aini; Siti Amiroch; Novita Eka Chandra (Unisda Journal of Mathematics and Computer Science (UJMC), 2020)
Purchasing data is very important for business actors because the data is very influential on companies, especially in the field of production and marketing. Therefore, the purchase data is one of the things that is kept secret by the business actors, such as PT Lamongan Marine Industry. With current technology hackers can easily hack such data, so the use of cryptography is a very appropriate solution to this problem. In this study the authors used the Vigenere Cipher algorithm and the RSA algorithm with a high security key. The hacker was not easy to find out the contents of the data. The data obtained is a purchase order, then presented in tabular form. The data is then encrypted and decrypted so that the comparison of the two algorithms is known. The results of the analysis state that the Vigenere Cipher algorithm is more effective in both encryption and decryption processing time. Ciphertext generated from the encryption process of the Vigenere Cipher algorithm is mostly in the form of punctuation, while the ciphertext generated by the RSA algorithm from the encryption process is mostly in alphabetical letters. The ciphertext generated by the RSA algorithm depends on the value of the modulo. but in terms of security the RSA algorithm is superior to the Vigenere Cipher algorithm.